2015
DOI: 10.1051/0004-6361/201425346
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the maser emission in the solar corona

Abstract: Aims. The electron plasma frequency ω pe and electron gyrofrequency Ω e are two parameters that allow us to describe the properties of a plasma and to constrain the physical phenomena at play, for instance, whether a maser instability develops. In this paper, we aim to show that the maser instability can exist in the solar corona. Methods. We perform an in-depth analysis of the ω pe /Ω e ratio for simple theoretical and complex solar magnetic field configurations. Using the combination of force-free models for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…ECM emission is a possible emission mechanism in the solar corona, but only at heights below 1.1 R in the active region studied. These results agree with Régnier et al [2015], where estimates of the ω p /Ω e ratio showed that ECM is possible at heights up to 1.2 R based on a sample of four active regions.…”
Section: The Location Of the Active Region Noaa 11785 On The Limb (supporting
confidence: 90%
See 1 more Smart Citation
“…ECM emission is a possible emission mechanism in the solar corona, but only at heights below 1.1 R in the active region studied. These results agree with Régnier et al [2015], where estimates of the ω p /Ω e ratio showed that ECM is possible at heights up to 1.2 R based on a sample of four active regions.…”
Section: The Location Of the Active Region Noaa 11785 On The Limb (supporting
confidence: 90%
“…Each beam produces a high time and frequency resolution dynamic spectrum (∼10 ms; 12.5 kHz) at a unique spatial location as shown in Figure 1b and 1c. The dynamic spectra can be used to produce tied-array images of radio bursts that can give an approximate position of radio sources (for more details see Morosan et al [2014;2015]). …”
Section: Observationsmentioning
confidence: 99%
“…The moving Type IV burst presented here starts its outward movement at 1.15 R , higher than the heights predicted by Régnier (2015) and Morosan et al (2016). Stupp (2000) proposed that the ratio ω p /Ω e can be as high as 2 for o-and x-mode emission, in which case it is possible for ECM to occur at greater heights in the corona.…”
Section: Second Component Of the Type IV Burstmentioning
confidence: 48%
“…They found that the LOmode dominates as harmonic modes are approached, resulting in emission angles corresponding to maximum growth, θ max < 15 • , that are therefore nearly aligned with the magnetic field. Régnier (2015) simulated the plasma emission properties of the solar corona above active regions using force-free models of the magnetic field together with hydrostatic models of the plasma. Similarly, he found that while the RX-mode dominates for ω p /Ω ≤ 0.35, LO-mode dominates for 0.35 ≤ ω p /Ω ≤ 1.…”
Section: J0607+24 Orientation Considerationsmentioning
confidence: 99%